John Wesley North and the Reform Frontier. - Stonehouse, Merlin (University of Minnesota Press, 1965)
This biography is the absorbing and significant story of a frontier life in America in the nineteenth century. John Wesley North was a carpetbagger in the best sense of the word, and professor Stonehouse points out that no fallacy is more persistent in Am.